Benefits of Management Systems Integration - Kafel , Piotr (Studia Oeconomica Posnaniensia, 2016)
The number of implemented and certified management systems in organizations is growing. In 2013 there were more than 1.1 million organizations with certified ISO 9001 management system. A big number of companies implement also other management systems and integrate them. The purpose of this paper is to analyze the benefits of integration of management systems in Polish organizations. The presented results are based on data obtained from 81 organizations that have implemented and certify at least two standardized management systems. The organizations were divided into 3 groups with different level of integration of implemented management systems. The level of integration was measured by the degree of integration of the system goals, resources and processes. As a top rated benefits of integration have been found such benefits as: Unification objectives, processes and resources, improving the effectiveness and efficiency of the organization and avoiding of duplication. Organizations that integrated their management systems on an average level, calculated as the integration of goals, procedures and documentation, achieve the greatest benefit from the integration process. Moreover, in the group of organizations, that integrated more than 3 management systems, benefits of integration were higher than in companies where only two or three systems were integrated.